Exponential of Sum/Real Numbers/Proof 6
Jump to navigation
Jump to search
Theorem
Let $x, y \in \R$ be real numbers.
Let $\exp x$ be the exponential of $x$.
Then:
- $\map \exp {x + y} = \paren {\exp x} \paren {\exp y}$
Proof
Fix $a \in \R$ and define the function $f_a : \R \to \R$ by:
- $\map {f_a} x = \map \exp {a - x} \exp x$
for all $x \in \R$.
We aim to establish that:
- $\map {f_a} x = \map \exp {a - x} \exp x = \exp a$
for all $a, x \in \R$.
Then, we can fix $x, y \in \R$ and set $a = x + y$ to obtain:
- $\map {f_a} x = \exp y \exp x = \map \exp {x + y}$
which is the claim.
Note that $f_a$ is differentiable and we have:
\(\ds \map {f_a'} x\) | \(=\) | \(\ds \map {\frac \d {\d x} } {\map \exp {a - x} } \exp x + \map {\frac \d {\d x} } {\exp x} \map \exp {a - x}\) | Product Rule for Derivatives | |||||||||||
\(\ds \) | \(=\) | \(\ds -\map \exp {a - x} \exp x + \exp x \map \exp {a - x}\) | Chain Rule for Derivatives, Derivative of Exponential Function | |||||||||||
\(\ds \) | \(=\) | \(\ds 0\) |
From Zero Derivative implies Constant Function, $f_a$ is constant.
That is, there exists $C \in \R$ such that:
- $\map {f_a} x = C$
for all $x \in \R$.
We have:
\(\ds \map {f_a} a\) | \(=\) | \(\ds \map \exp {a - a} \exp a\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \exp 0 \exp a\) | ||||||||||||
\(\ds \) | \(=\) | \(\ds \exp a\) | Exponential of Zero |
So:
- $\map {f_a} x = \exp a$
for all $a, x \in \R$.
That is:
- $\map \exp {a - x} \map \exp x = \exp a$
for all $a, x \in \R$.
Hence the result.
$\blacksquare$